2005
DOI: 10.1164/rccm.200501-146oc
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase Improves Gas Exchange and Pulmonary Hemodynamics in Premature Lambs

Abstract: Rationale: Oxidant stress may increase the severity of respiratory distress syndrome (RDS) after premature birth by altering vasoreactivity and increasing lung edema, but the acute effects of superoxide dismutase (SOD) treatment on gas exchange, lung compliance (CL), and pulmonary vascular resistance in premature animals with RDS are unknown. Objective: We studied the effects of intratracheal recombinant human SOD treatment (rhSOD) on gas exchange, CL, and pulmonary hemodynamics in 46 premature lambs with RDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…[23]. In contrast, a number of studies performed in disease models of chronic pulmonary hypertension, such as the ductal closure in preterm lambs, group B streptococcal- induced pulmonary hypertension in newborn lambs, or monocrotaline-induced pulmonary hypertension have found that SOD treatment did not alter, or even blunted vasoconstriction [1, 31, 32]. Other published studies are consistent with our observation that in the systemic circulation, SOD activity can enhance vasodilation.…”
Section: Discussionsupporting
confidence: 87%
“…[23]. In contrast, a number of studies performed in disease models of chronic pulmonary hypertension, such as the ductal closure in preterm lambs, group B streptococcal- induced pulmonary hypertension in newborn lambs, or monocrotaline-induced pulmonary hypertension have found that SOD treatment did not alter, or even blunted vasoconstriction [1, 31, 32]. Other published studies are consistent with our observation that in the systemic circulation, SOD activity can enhance vasodilation.…”
Section: Discussionsupporting
confidence: 87%
“…Hypoxemia in the premature lamb model is a result of several factors, the most important being decreased oxygen uptake due to surfactant deficiency, PH, and intrapulmonary and extrapulmonary shunts (4,13,19,22). Surfactant was administered before initiation of ventilation resembling prophylactic surfactant administration in human infants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, infants born prematurely and treated with recombinant human copper-zinc superoxide dismutase (CuZn-SOD) had improved pulmonary function and reduced hospitalization rates at one year of corrected age (8). Furthermore, recombinant human CuZn-SOD and overexpression of extracellular (EC)-superoxide dismutase (SOD) in alveolar type II epithelial cells have been shown to preserve lung development in preterm lambs and newborn mice, respectively, that had been exposed to high levels of oxygen at birth (1,2,24,27). Lung-specific overexpression of EC-SOD has also been shown to prevent influenza-induced lung injury in adult mice (40).…”
mentioning
confidence: 99%